2016
DOI: 10.1186/s13104-016-2310-1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance of nosocomial infections in the Yaounde University Teaching Hospital, Cameroon

Abstract: BackgroundNosocomial infections (NI) represent a real public health problem in developing countries. Their surveillance is recommended to provide needed information for better control. The aim of this study was to describe the frequency and distribution of NI in the Yaoundé University Teaching Hospital (YUTH).MethodsIt was a longitudinal and descriptive study targeting hospitalized patients in the intensive care, gynaecological, surgical and neonatal units. Each consenting patient was administered a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
3
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 14 publications
1
23
3
3
Order By: Relevance
“…Elsewhere a study from Kawolo General Hospital in Uganda reported, S. aureus with the highest prevalence 46/61 (75.4%) [10]. On contrary our findings are different for some studies carry out in Cameroon (surveillance of nosocomial infections in YUTH) and Uganda (contamination of microbial pathogens in 4 operating theatre), where Klebsiella spp (27%), Pseudomonas spp (23.9) and Bacillus spp (17.5%) were found as common organisms respectively [6,11]. This difference can be due to the type and level of target hospital, units, type of specimen (hospital environment & hospitalized patients) and sample size.…”
Section: Results Of Culture According To the Profile And Prevalence Ofcontrasting
confidence: 81%
See 2 more Smart Citations
“…Elsewhere a study from Kawolo General Hospital in Uganda reported, S. aureus with the highest prevalence 46/61 (75.4%) [10]. On contrary our findings are different for some studies carry out in Cameroon (surveillance of nosocomial infections in YUTH) and Uganda (contamination of microbial pathogens in 4 operating theatre), where Klebsiella spp (27%), Pseudomonas spp (23.9) and Bacillus spp (17.5%) were found as common organisms respectively [6,11]. This difference can be due to the type and level of target hospital, units, type of specimen (hospital environment & hospitalized patients) and sample size.…”
Section: Results Of Culture According To the Profile And Prevalence Ofcontrasting
confidence: 81%
“…This can be supported by a study that reported the presence and increase of MRSA in Many hospitals of several countries in Africa [24]. On the contrary our findings are different from the studies of Nouetchognou et al and Bashir et al who conducted in and Yaounde University Teaching Hospital in Cameroon and three tertiary hospitals, Kano state, Nigeria, where Klebsiella spp were the most frequently isolated bacterial nosocomial pathogens from all units and all studied hospitals respectively [6,25].…”
Section: Profile and Prevalence Of Bacteria Isolated According To Thecontrasting
confidence: 52%
See 1 more Smart Citation
“…En nuestra institución, 39,1% de las ITU-AAS fueron ITU-noC, constituyendo un porcentaje no despreciable dentro de las ITU-AAS. Dentro de la poca bibliografía que ha comparado ambos tipos de ITU-AAS, se ha reportado una frecuencia cercana a 30% de ITU-noC 7,10 . De este modo, se denota la importante frecuencia de dichas infecciones en nuestra institución, adquiriendo un valor epidemiológico de gran importancia.…”
Section: Discussionunclassified
“…L as infecciones urinarias asociadas a la atención de la salud (ITU-AAS) representan un importante problema de salud pública, estando asociadas a incremento de la morbimortalidad de los pacientes, días de internación y costos en salud [1][2][3][4][5][6][7] . Múltiples reportes mencionan a las infecciones urinarias como la infección más frecuente dentro del ámbito hospitalario 6,8,9 . El conocimiento de los factores de riesgo asociados y el perfil de susceptibilidad de los microorganismos causantes de las mismas son herramientas indispensables para generar guías de tratamiento adecuadas.…”
Section: Introductionunclassified